Projeto de um conversor CC-CA trifásico para interligar um sistema fotovoltaico à rede elétrica - Ximenes, Saulo Castro (2012)
Currently, there are several manufacturers in the international market of static converters for photovoltaic infrastructure. In Brazil, by there is no product with a national technology to reach this niche market, is important and urgent to develop national technology in the field of DC-AC converters to PV systems. The present work consists of developing of a three-phase AC-DC converter with the purpose of connect a PV system to the electricity grid, where the main objective of this system is to provide active power for the three-phase electrical system. This three-phase AC-DC converter is composed of a stage of DC-DC conversion, which consists in a boost converter, and a stage of DC-AC conversion. The choice of converter topology considered some criteria, such as low cost of acquisition and maintenance, low complexity, high compaction and reliability. The modeling and control of the converter are made using the concept of space vector, in the other words, using the dq0 transform direct and inverse. This control was performed in a digital signal controller (DSC) of dsPIC family. The design of the controllers of both stages was done digitally. Through simulation was validated the operation of the converter and its controllers designed. For the experimental tests some design changes had to be made because there was a significant amount of electromagnetic interference and noise generated by the prototype during its operation. From the conditions established was possible to inject into the electricity grid a just over 40% of the maximum value of power specified. The experimental results from the prototype validated the control algorithm implemented in the converter, being injected into the electricity grid sinusoidal currents with low harmonic content and frequency of the brazilian electrical system.